2015
DOI: 10.1039/c4cp05020g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of water-dispersible porous g-C3N4 with improved photocatalytic activity by chemical oxidation

Abstract: Hydrophilic treatment of bulk graphene-like carbon nitride (g-C3N4) for future applications has aroused extensive interest, due to its enhanced specific surface area and unusual electronic properties. Herein, water-dispersible g-C3N4 with a porous structure can be obtained by chemical oxidation of bulk g-C3N4 with K2Cr2O7-H2SO4. Acid oxidation results in the production of hydroxyl and carboxyl groups on its basal plane and the formation of a porous structure of g-C3N4 at the same time. The porous g-C3N4 appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
111
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(126 citation statements)
references
References 59 publications
14
111
0
1
Order By: Relevance
“…The characteristic peaks for the acid-treated samples were similar to those of the bulk structure, indicating that g-C 3 N 4 had the same chemical composition even after exfoliation and conversion of the morphology. The many small peaks observed in the range of 1200–1650 cm −1 correspond to stretching vibrations of C=N, C–NC–C or C–N–C bonds of C–N heterocycles4950. The presence of these bands confirmed that the basic surface functional units were retained after the acid and thermal treatments.…”
Section: Resultsmentioning
confidence: 79%
“…The characteristic peaks for the acid-treated samples were similar to those of the bulk structure, indicating that g-C 3 N 4 had the same chemical composition even after exfoliation and conversion of the morphology. The many small peaks observed in the range of 1200–1650 cm −1 correspond to stretching vibrations of C=N, C–NC–C or C–N–C bonds of C–N heterocycles4950. The presence of these bands confirmed that the basic surface functional units were retained after the acid and thermal treatments.…”
Section: Resultsmentioning
confidence: 79%
“…43,44 In contrast, the peak corresponded to C-OH became much stronger for the O-g-C 3 N 4 monolayer (532.1 eV), suggesting that more C-OH groups were generated in O-g-C 3 N 4 monolayer after the oxidation cutting. Beside the O 1s peak at 532.1 eV, a new peak at 533.0 eV has been detected, which refers to the O=C.…”
Section: Resultsmentioning
confidence: 80%
“…The FTIR spectra of the bare g‐C 3 N 4 show that the broad peak from 3274 cm −1 to 3078 cm −1 is the corresponding stretching modes of N‐H bonds . The small bumps in the range of 1200 cm −1 ‐1650 cm −1 related to stretching vibrations of (C=N, C‐NC‐C or C‐N‐C bonds) CN heterocycles A tiny peak at 878 cm −1 was matching to the stretching mode of the N‐O group . The sharp peak observed at 806 cm −1 assigned to the breathing modes of triazine units .…”
Section: Resultsmentioning
confidence: 97%